2016
DOI: 10.3389/fpls.2015.01230
|View full text |Cite|
|
Sign up to set email alerts
|

Melatonin: Current Status and Future Perspectives in Plant Science

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) is a ubiquitous molecule with pleiotropic actions in different organisms. It performs many important functions in human, animals, and plants; these range from regulating circadian rhythms in animals to controlling senescence in plants. In this review, we summarize the available information regarding the presence of melatonin in different plant species, along with highlighting its biosynthesis and mechanisms of action. We also collected the available information on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
209
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(227 citation statements)
references
References 107 publications
(141 reference statements)
7
209
0
Order By: Relevance
“…This growth promotion phenotype was evident both in 7‐day‐old seedling grown in MS medium and in 45‐day‐old rice plants grown in the field . Observations in ovine SNAT transgenic plants confirmed the growth‐promoting roles of melatonin, which had long been observed in several plant species in response to exogenous melatonin treatment . However, the current OsSNAT1 transgenic rice plants lacked such seedling growth promotion effects both in vitro and in vivo in the field (Figure and ) although OsSNAT1 transgenic rice plants produced melatonin at levels comparable to those seen in ovine SNAT transgenic rice plants.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This growth promotion phenotype was evident both in 7‐day‐old seedling grown in MS medium and in 45‐day‐old rice plants grown in the field . Observations in ovine SNAT transgenic plants confirmed the growth‐promoting roles of melatonin, which had long been observed in several plant species in response to exogenous melatonin treatment . However, the current OsSNAT1 transgenic rice plants lacked such seedling growth promotion effects both in vitro and in vivo in the field (Figure and ) although OsSNAT1 transgenic rice plants produced melatonin at levels comparable to those seen in ovine SNAT transgenic rice plants.…”
Section: Discussionsupporting
confidence: 63%
“…Since the first discovery of melatonin in plants in 1995, many pharmacological studies have been performed to investigate its functional and physiological significance . Large numbers of experiments involving exogenous application of melatonin to a series of plant species indicated that melatonin acts as a biostimulator in plants by enhancing a myriad of defense responses against abiotic stresses, including oxidative stress, high temperature, cold, senescence, drought, and salt, as well as biotic stress such as pathogen attacks .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several highly relevant differences in the melatonin biosynthetic genes between animals and plants were identified through comparisons with the melatonin synthetic capacity in the heterologous E. coli system. When the plant SNAT gene was first cloned from rice (Kang et al 2013), the purified recombinant SNAT protein had fivefold lower enzyme activity than that of animals, even though the levels of melatonin production are higher in plants than in animals (Voisin et al 1984;Nawaz et al 2016). Thus, clear-cut evidence of a role for a cloned plant SNAT gene in the direct synthesis of melatonin in vivo would be invaluable for heterologous systems such as E. coli.…”
Section: Discussionmentioning
confidence: 98%
“…Exogenous melatonin can act as a phytoregulator of seed germination (Zhang et al, 2013, 2014), flowering (Kolář et al, 2003), fruit ripening, anthocyanin accumulation (Sun et al, 2016), root system architecture (Pelagio-Flores et al, 2012), chlorophyll preservation, and leaf senescence (Zhang et al, 2016). It is also a powerful antioxidant that directly decreases the levels of ROS or indirectly modulates antioxidant enzyme activities (Posmyk et al, 2008, 2009; Arnao and Hernández-Ruiz, 2009; Nawaz et al, 2016). Abiotic stressors can elevate the levels of endogenous melatonin in plants (Arnao and Hernández-Ruiz, 2013a,b, 2016; Shi et al, 2015), so stress-induced ROS may trigger melatonin accumulation (Arnao and Hernández-Ruiz, 2015).…”
Section: Introductionmentioning
confidence: 99%